Anatomy of the peritoneum: theoretical problems in the applied aspect - A. I. Shvedavchenko; V. A. Kudryashova; M. V. Oganesyan (Сеченовский вестник, 2022)
In peritoneal cavity authors distinguish upper and lower stories, the vault (fornix) and the bottom (fundus). The upper storey is divided into four spaces: right and left parahepatic, pregastric and omental bursa. In the right and left parahepatic spaces we allocate suprahepatic and infrahepatic pouches. The lower (subcolic) storey of peritoneal cavity is subdivided into two parts: anterior, preomental fissure and posterior, retroomental space.